A Conceptual Model of Behavioral Factors Affecting the Adoption of E-government Services in Macao SAR - Iong, Kit Yeng (University of Saint Joseph, 2022)
Information and communication technologies (ICTs) are highly associated with the study of e-government, and many scholars believe that within the coming decades, government operation and policy decision-making cannot persist without the use of ICTs (Van Dijk, 2018). This thesis aims to generate a conceptual framework of the behavioral factors that could contribute to the acceleration of the implementation of e-government services in Macao SAR. Rather than regarding e-government services as a goal to be realized in traditional practice through evaluating the outcome, a process-oriented study was conducted. The e-government services are regarded as advanced tools in the 21st century to transform Macao into a smart city. The design of the process-oriented approach and the comparative study of four groups of Macao citizens' behavioral intentions are solidly supported by the research gaps identified in the literature review of e-government studies in an international perspective and the actual context of local Macao studies. Under the framework of the Theory of Planned Behavior (Ajzen, 1985, 1991), the behavioral factors of the general public and civil servants are investigated through a qualitative approach, and the findings are triangulated from various aspects. Firstly, a systematic literature review of TPB was conducted thoroughly to better understand the current study of e-government around the world. Secondly, a content and thematic analysis of the official documents and articles from local press media and research institutes related to the topic of e-government services was carried out to demonstrate a more comprehensive picture of the current problems of implementing iv and adopting e-services in Macao SAR. Observations in some government premises that provided e-services and 40 in-depth interviews were conducted to generate detailed and first-hand data. Key issues were extracted from the interviewees’ narratives and daily actual usages. Different conceptual models for different age groups and civil servant group were formed. Special attention was paid to analyzing the "hard-to-reach" groups' behavioral intentions. Research limitations identified from the previous literature were overcome partially in this study too. After comparing the similarities and differences, a new conceptual model of significant behavioral factors that affect the behavioral intentions in adopting e-government services was built. Results and findings from the analysis could be used to develop effective interventions by the government policymakers in responding to the behavioral change of the general public in the aspect of e-government services acceptance and adoption
Keywords: Thesis and Dissertations PhD in Government Studies (D-GS); University of Saint Joseph

A Financial Valuation of Netflix, Inc - Tong, Si Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Realty Income Corporation - Rodrigues, Ricardo David Almeida Fernandes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Under Armour - Leong, Ka Wa (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Historical Invertigation into the Pentecostal and Charismatic Movement in Macau's Protestant Churches: From Thomas J. Mcintosh to the Present Day - Ho, Kei Tsui (University of Saint Joseph, 2022)
This dissertation is a comprehensive academic examination of the characteristics and complex historical progress within the Pentecostal and Charismatic Movement in Macau Protestant Churches. Since Macau hosted the first Pentecostal and Charismatic missionary, Thomas J. McIntosh, who entered China in 1907, the history of the Pentecostal and Charismatic Movement in Macau lacks a consistent and synthesized research until now. Thus, primary and secondary resources have been analyzed and reconstructed and historically interpreted to gain a better and deeper understanding of the emergence and development of the Pentecostal and Charismatic Movement within Macau’s Protestant Churches from the beginning up to the present day. This academic review makes an important contribution to Macau with respect to its historical development and will fill the gap in knowledge within the Global church history of the Pentecostal and Charismatic Movement. Key Words: Charismatic, Christianity in China, History of Missionaries in China, Macao, Macau, Pentecostalism, Protestant, T. J. McIntosh
Keywords: Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

A Psychological and Phenomenological Analysis of Chinese People Who Are Not-Capable-Of-Saying-No - Song, Sok Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

A Qualitative Exploration of the Learning and Teaching Experiences of Teachers Who Completed A Post-Graduate Early Childhood Diploma in Macau =: 探討澳門學位後幼兒教育文憑教師的學習體驗及其教學實踐之質性研究 - Ieong, Weng Ian (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Qualitative Research on The Career Choice, Current Situation and Prospects of Preschool Tutors Working in Nursery Schools and Kindergartens in Mainland China, Taiwan and Macau=: 中國內地、台灣、澳門幼兒導師從事托兒所和幼兒園工作的職業選擇、現況和前景之質性研究 - Lai Ka Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Qualitative Research on Tutors' Attitudes Towards the Implementation of the Emotional Eduation in Macau Nurseries =: 澳門托兒所導師對幼兒情緒教育態度的質性研究 - Chan, Man Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Research study on the relationship between work stress and well-being of primary school teacher in Macau =: 澳門小學教師的工作壓力與幸福感之相關研究 - U, Ka Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study of Primary School Students’ Motivation to Learn English as a Foreign Language in the Context of Content and Language Integrated Learning (CLIL) – A Case Study - Pau Ka Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A STUDY OF PRIMARY SCHOOL TEACHERS' TEACHING PROBLEMS AND THEIR COPING STRATEGIES FOR TEACHING INCLUSIVE STUDENTS IN MACAO =: 澳門小學教師面對融合學生的教學困擾及其因應策略之研究 - Hoi Ka Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study of the Macau personal data protection legal regime - Cabanos, Leilani Oliver (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

A Study of the Macau Personal Data Protection Legal Regime - Sun, Wai Lon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

A Study of the Professional Development of Mid-High Level Management Personnel of Non-Tertiary Education in Macau=: 澳門非高等教育中高層管理人員專業發展之研究 - Leong, Ka Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A study on Children's Learning Evaluation in Macao Kindergarten——Taking a Kindergarten in Macao as an example =: 澳門幼師對幼兒學習評量之研究——以澳門某幼稚園為例 - Chan Ka Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study on inclusive Class Management by Nursery Teachers in Macau =: 澳門托兒所融合班教師班級經營之研究 - Fong, Ka Lei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study on Spiritual Well-Being of Secondary School Teachers in Macau - Wong, Kuan Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Study on the Peer Relationship of Students Aged 9-12 with Special Educational Needs in Macao=: 澳門九至十二歲融合生與同儕關係之研究 - Hong Mei Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Study on the Relationship Between Positive Emotions and Work Stress in Private Kindergarten Teachers in Macau=: 澳門幼稚園教師正向情緒與工作壓力關係之研究 - Chan, Hio Tong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Research on Drawing Guidance as an Intervention to Improve Chinese Writing of Primary Students with Dyslexia =: 繪畫活動介入引導讀寫障礙學生提升寫作能力之行動研究 - 黃郁羚 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Research on the Influence of Flipped Classroom on Learning Achievement and Learning Motivation of Primary School Students in Programming Courses=: 翻轉教學對於小學程式設計學習成效與學習動機影響之行動研究 - Choi, Wan Chong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Action Study of Using Game-Based Learning into English Learning to Improve the Lerning Outcomes of Primary Level Students in Macau =: 遊戲式教學融入澳門小學低年級英語課程以提升學生學習成效之行動研究 - Hsu, Hsiao Chien (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Analysis of Celebrities and KOLs Influence Consumer Decisions on the Luxury Fashion Market in Macau - Ip, San U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study of Macao's role as arbitration seat for commercial disputes between China and portuguese-speaking countries - Leung, Cheok Si (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

An Investigation into Play-Based Educational Support For The Developing Social-Communication Skills in Children with Autism Spectrum Disorder (ASD) in Kindergarten - Cheong, Tânia Guilherme (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An Investigation on Macao Children with ASD and their Families needs on Social Support - Chau, Chin Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Analysis of the Impact of Environmentally Sustainable Practices on Macau Hotels Guest Engagement - Santos, Ana Sofia Kong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Applying Social Skills Improvement System Intervention Guide to Primary Students with ADHD and Problem Behaviors in Macau: A Case Study - Ung, Hou Cheang (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

Art-Based Intervention For Children with ADHD: Catina Fong Chi Cheng - Fong Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Assessment of Methodologies Employed by Change Agents in Managing Organizational Change: A Case Study in the Hospitality-Gaming Industry - Tagulao, Thea Clarice Saavedra (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Career Development of People with Physical or Sensory Impairments in Macau - Ma I Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

CASE STUDY ON ART INTERVENTION WITH CHILDREN WITH AUTISM SPECTRUM DISORDER - Wu, Hoi Pio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Children's Learning Interest and Social Interaction Through Play: An Action Research Case Study in A Pre-School in Macau= 運用遊戲活動增進幼兒學習興趣與社交互動之行動研究 - 以澳門一幼兒班為例 - Tang Pui I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Classroom Supports For Primary 5 to Form 3 Students with Emotional and Behavioural Challenges: A Case Study Approach - Lao, Pek Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Clothing and School Uniforms in Macau: Maria João Nunes Das - Das, Maria João Nunes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

COP21 COMPLIANCE AND SUSTAINABLE DEVELOPMENT THROUGH INTEGRATED SOLID WASTE MANAGEMENT: IMPLEMENTATION PERSPECTIVES OF THE CIRCULAR ECONOMY IN THE PEARL RIVER DELTA AREA - Li, Warren Man Ho (University of Saint Joseph, 2022)
The global living standard improved significantly in the last decades and China moved 800 million people out of poverty since 1980. However, production and consumption in their current forms are unsustainable in matters of resource and energy use and involved emissions with their significant ecological impact. The global human community committed itself in the COP21 Agreement of Paris 2015 to reduce Green House Gas (GHG) emissions based on National Determined Contributions (NDCs) in order to limit the increase of global average temperature below 2°C or better 1.5°C above pre industrial levels. This commitment entails a comprehensive transformation of the current social and economic system in view of decoupling economic growth from both resource extraction and GHG emissions, in view of fostering a resource sensitive and CO2 neutral Circular Economy (CE) based on Sustainable Development (SD). China submitted its first Intended Nationally Determined Contributions (INDCs) in 2015 with policies and measures affecting 15 major areas. In 2020, President Xi Jinping announced the commitment to peak China’s carbon dioxide emissions before 2030 and achieving carbon neutrality before 2060. Proper and Integrated Resource and Waste Management is central on the way to achieve the transformation into a CE. The State Council of the People’s Republic of China (PRC) released its plan “生活垃圾分类制度实施方案” to promote source separation of household waste on March 30, 2017 aiming at the recycling rate for household waste to reach 35% by 2020 for the selected cities. The first China’s Mandatory Waste Source Separation Law “廣州 市生活垃圾分類管理條例” was enforced by the city of Guangzhou on July 1st, 2018. One of the key strategic plans in China is the development of the Greater Bay Area (GBA) with its comprehensive development plan released on February 18, 2019. Following the INDCs by China, parts of the GBA Development Plan emphasize that the development of the CE systems and the implementation of extended producer responsibility (EPR), are effective principles to provide financial incentives in view of reducing embedded emissions in material and processes. The present research studied, analysed, and compared the MSW treatment strategies, rules, regulations, and retrievable data, which lead to MSW source separation and the reverse logistic of separated waste among 4 selected cities Guangzhou, Zhuhai, and the 2 S.A.R.s of Hong Kong and Macao. The experience and comparison from Guangzhou and Hong Kong revealed that a Top-down approach in environmental policy decision making is more efficient and is able to implement necessary policies faster. However, the experiences from Guangzhou and Zhuhai indicate, that also a more participatory implementation process is crucial, as it enables the involved stakeholders to express their experiences and opinions properly, which can lead to a higher level of policy feasibility and acceptance and a smoother operation accompanied with a higher effectiveness. For the two SARs, to achieve the objective to increase the recycling rate, the local Government must seek approval from China’s Central Government to allow locally generated recyclable material, in their original form, to enter mainland China for further treatment and to be turned into secondary raw material. Without such a proper support by a reverse resource logistic from the mainland, the CE schemes, such as the Mandatory Waste Source Separation, Producer Responsibility Scheme (PRS), Waste Charging Scheme, are not able to be implemented effectively. The current approach of the Local Government purchasing of recycling and exportation services of recyclable materials from private companies, and the sole reliance on existing market forces to handle, process, and export recyclable material out of the S.A.R.s cannot ensure a reliable and continuous operation in view of mitigating involved emissions. By way of a comparative analyses, the present investigation works out and distils suggestions for best practices of implementing the CE to comply with targets of emission reductions
Keywords: Circular Economy (CE); Sustainable Development Goals (SDGs); Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph; Waste Hierarchy; Zeroand- Low-Waste-Systems

Crisis Management – Dystopic Scenario VS Real-World Pandemic: The Case of Saramago’s Blindness that Anticipated the Initial Managerial Approach to Covid-19 Pandemic Taken by Unprepared Governments Worldwide - Rouxinol, Hernâni Tiago Caveirinhas (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

E-Commerce in the Hospitality Industry: The Online Hotel Booking and Digital Marketing in Macau - Chowdee, Nattiya (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Enhancing Secondary Students' English Language Skills and Engagement through Cooperative Learning: An Action Research Study - U, Tat Si (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Environmental Education in Macau’s Schools: A Case Study on Teachers' Perceptions of Experiential Pedagogies - Reh, Paul Thu (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Expansion of private tutoring centers in Macau: voice from parents of primary school students - Fong, Chan Seng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Experience the Past in the Present with Immersive Technologies Case Study: “The Old Ladies’ House”, Albergue, Macau - Chang, Tin Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Exploratory Case Study of Teacher's Perspectives in Assisting Students with Special Needs in Inclusive Schools in Macau - Diakité, Patrícia Dina Correia Silves Ferreira (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Current Collaboration Practices of Regular and Resource Teachers within Inclusive Education: An Analysis of Teacher Perspectives - Loi, Sio Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Differentiated Teaching in Primary Mathematics Classes in Macau - Pearce, Josef Nicolai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Macau Instagrammers’ Motivation for Using Instagram Story - Wong, Choi I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Exploring Teachers' and Students' perceptions in Formative Assessment Through Project-based Learning for Students Included in Mainstream Schools - Lei, Lei Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring Teachers' Experiences and Perceptions of the Use of the IEP with Students with ASD in Primary Schools - Lei, Mei Seong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring the Application of Online Learning Environment in the Teaching and Learning of Chinese in Elementary Education Sector in Macau=: 探討網上教學摸式在澳門小學中文科教與學的應用 - U Ka Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring The Influence of Culture on Parents’ Attitudes Towards Inclusive Education in Macao - Moreira, Irene Mitsiko Sadoyama (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring the Problems and Strategy Use by Primary School Teachers in Conducting Classroom Management Under the Policies of Inclusive Education in Macau =: 探討澳門融合教育政策下小學老師面對班級經營的困難及策略 - Lam Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Factors Influencing Disability Inclusion Practice in Social Media: A Case Study of MDA Service Centre for the Deaf - Chan Wai Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Feasibility study of a Glamping Business in óbidos, Portugal - Sousa, Eugénio Ricardo de (University of Saint Joseph, 2022)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Fintech Services in Guangdong-Macao in Depth Cooperation Zone in Hengqin: An investigation of Macao Users' Adoption - Kuan, Chi Hou (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

General Teachers’ Attitude Towards Inclusive Education in Students with Dyslexia in High School Students=: 中學普通班教師對患有讀寫障礙學生的認識與其融合教育的態度 - Hong, Yufang (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

How Does Employer Brand Affect Employer of Choice? A Case Study of Two Macau F&B Groups’ Employer Branding Comparisons - Chen, Zhi Yi (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

How Might We Provide Students with Agility and Digital Literacy? Case Study of the Bachelor of Communication and Media at the University of Saint Joseph - Cathagne-Benventi, Sophie (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Illegal Immigration and Population Police in Macau: A Case Study of Fujianese Immigrants = 澳門非法移民問題及其治理——以澳門的福建移民為例 - Lam Lai Teng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Influencer Industry Development in Macau: Case Study about Social Media Influences in Macau - Madan, Roberto (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Integrative Educational Platform Focusing on Steam Approaches: A Macau Case-Study - Un Man Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Intention Towards Online Counseling among Service Provider in Macau=: 澳門社會服務提供者對應用線上輔導的意向 - Lao, Hoi Keong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Job Satisfaction, Dilemmas and Causes of Hearing Impaired People in Macau =: 澳門聽障人士工作滿意度、困境及其原因 - Pang, Wan I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

Knowledge and Attitude of Parents with Regular Primary Children Towards Inclusive Education in Macau =: 澳門小學普通生家長對澳門融合教育的認識及態度之調查報告 - Chong, Leng Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

LIFE CYCLE ASSESSMENT OF CONSTRUCTED WETLAND SYSTEMS FOR TOURISM UNITS WASTEWATER TREATMENT - Lo, Weng In (University of Saint Joseph, 2022)
With water being an essential for life on Earth, it is vital to preserve it and regenerate it, in order to be available for a myriad of uses. Though many types of wastewater management and treatment are available, most rely on high energy input and are therefore not ideal for many circumstances. Constructed wetlands (CW) are an alternative nature-based solution to be applied to wastewater treatment. This study undertakes a Life-Cycle Assessment (LCA) of a CW as a means of wastewater treatment and aims to understand how these systems can be an environmentally conscious alternative. The CW under study is located in a rural mountain area in the north of Portugal. Receives wastewater from a tourism unit and operates with horizontal subsurface. The LCA analyses the CW through the construction, operation (treatment), and composting phases. This approach allows the entire scope of the life cycle to be included, of which, the composting phase has been absent in similar LCA previously undertaken. Analysis focuses on the impact categories: Ozone Layer Depletion Potential, Global Warming Potential, Acidification Potential, Eutrophication Potential and Human Toxicity Potential. Of the five categories, none increase during the treatment phase, and indeed, Acidification Potential, Eutrophication Potential, and Human Toxicity potential all decrease. Ozone Layer Depletion Potential and Global Warming Potential increase significantly during the construction and composting phases respectively. Both can be rationalized, with the former being a result of heavy diesel machinery use in construction and the latter a natural byproduct of composting. The results are net positive and display the ability for CW as a low energy wastewater treatment which can limit environmental impact by choice of construction and composting methodology
Keywords: Lifecycle assessment; Master of Environmental Sciences and Management (MESM); University of Saint Joseph; constructed wetland; wastewater treatment

Lighting Up A Place with Good Stories: Heritage Interpretation Strategies and the Macau Historic Centre - Ip, Kin Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

LISTENING TO CHILDREN’S IDEAS TO IMPROVE IN LEARNING AND DEVELOPING HIGHER-ORDER THINKING SKILLS THROUGH REFLECTION WITH DAILY DOCUMENTATION - Ae, Young Choi; Ho, Ka Lee Carrie (University of Saint Joseph, 2022)
Listening to children’s voices is still not considered an essential part of education in some schools, including many in Asian countries. The authority of schools and teachers is still highly valued under the continued influence of Confucian Heritage Culture in many Asian schools, including a significant number in Macao. Teachers in international schools in Asian countries often experience some difficulties when communicating with young children because of their low English proficiency and the traditional views supported by many parents who grew up with the Confucian Heritage Culture, which encourages children to be quiet in the classroom to be good listeners. This Action research took fifteen months between two school years, 2018- 2019 and 2019-2020, with two groups of four and five-year-old students in a kindergarten classroom. Documentation posters were created for young children to use the next morning to reflect on their learning. The pedagogy of listening and pedagogical documentation from the Reggio Emilia approach were implemented to discover and record young children’s ideas and interests, work with daily documentation posters, and help them reflect on documentation posters to improve their learning and develop their higher-order thinking skills. Photos and videos, observation notes with the children’s comments, documentation posters, and reflective discussions were used as interventions to collect the children’s ideas and record their learning activities. The children learned to use documentation posters to remember, think, share, and improve their learning. The children’s comments from Learning Centres, recess, and reflective discussions were used to examine their understanding of learning and higher-order thinking skills. During one Pilot Cycle and three structured data collection cycles, the children demonstrated improvement in learning for each learning project and development of their thinking skills both with and without the teacher’s support. The children demonstrated higher-order thinking skills more often from Learning Centres and recess when they had to solve problems. They also demonstrated higher-order thinking skills more often during the whole group reflective discussions than in small group reflections, when a bigger number of children joined or when they had enough time to think. The thinking skills when children were reflecting were observed to concentrate on remembering and understanding as they focused on remembering and sharing the previous day’s work. The children’s other higher-order thinking skills did not show an increase in frequency during reflective discussions. However, the children demonstrated active engagement and a range of higher-order thinking skills when the teacher asked openended questions and provided support and comments to help them to connect their learning to their past experiences. Findings indicated that the children’s learning from each Learning Centre showed change and improvement during their play over time according to their interests, indicated by their material use and comments. The research was limited by its small number of participants within their age group due to convenience sampling and the children’s relatively limited ability to demonstrate higher-order thinking skills. This study has shown how teachers could help children use daily documentation posters to develop their learning and thinking skills by visualizing their ideas and the teacher’s important role in supporting children’s learning with active listening and support in the classroom
Keywords: Bloom’s Taxonomy; Early Childhood Education; Pedagogical Documentation; Reggio Emilia Approach; Thesis and Dissertations PhD in Education (D-SE); University of Saint Joseph

Macau's Historical House Taxonomy: The Shophouses at the Rua de Cinco de Outubro (Case Studies) - Fu Ho I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

Macau Secondary School Teachers’ Attitudes Towards Inclusive Education and Concern Over It =: 澳門中學教師對融合教育的態度與憂慮之研究 - 陳瀅瀅 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Mandatory Provident Fund Scheme: Prespectives of Macau Employees - Cheong, Kit I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Maternal Postpartum Experience in Macao: The Relationship Between Demographics, Income, Social Support and Postpartum Depression - Bonthuis, Ana Maria Barradas Leitão Abril (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Moral Self-Regulation or Consistency: The Role of Cultural Values and Workplace Status - Leong, Kin Hei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Motivations of preservice teachers: a case study on career changers to teaching in Macau - Thang, Tony Mana (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

New Great Learning Oneness Epistemic Model for the Greater Peace: A Philosophical Analysis on the Concept of Oneness and its Application with Veganism - Hun, Kuong U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Online Gaming with Digital Currencies: A Comparative Legal Study - Chan, Ka Yuen (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Lusophone and International Public Law(MLIPL); University of Saint Joseph

Palate Consciousness: A Philosophical Analysis on the Cultivation of Gustatory Aesthetics Through the Framework of Phenomenology of Perception - Chiang, I. Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Parental Perspectives on Inclusive Education in Macau - Leong, Ka Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parental Stress and Marital Satisfaction in Macao: The Mediating Effect of Parental Involvement - Wong, Pek Ieng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Park-meter: Designing an Innovative Macau System - Cheang, Chi Tat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Design (MDG); University of Saint Joseph

Perception About Challenges and Opportunities of Social Enterprise in Macau - Wong, Chong Chio (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

Perspectives and Practices of Macau Secondary School Teachers Regarding ICT in Teaching and Learning - Das, Amit (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Problematic Internet Use and Subjective Wellbeing Among University Students in Macao - Kam, Chi Fat (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Project-based Learning in the Subject of General Studies in a Grade Five Class: A Case Study Approach - Chan, Ka Ho (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Redefining Macau's Film Industry: Case Studies on local Film Marketing & Distribution - Choi Chi Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Relationship Between the Academic Achievement and Extra-curricular Tutoring of Primary Students: Perspectives From the Parents = 課外補習與小學生學業成績之間的關係----來自家長的視角 - Vong, Sok Kuan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Self-perception of primary students with dyslexia in Macao =: 探討澳門小學讀寫困難融合自我探索學習現況及挑戰 - 何素儀 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Study of management style in Canada - Ao, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Teacher Efficacy: Inclusive Practice to Support Learning English as a Foreign Language (EFL) among Chinese-Speaking Students with Dyslexia in Macau - Oksana, Zorina (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teachers’Perceptions of Performance Appraisal in a Secondary School in Asia: A Case Study - Potger, Matthew Rodney (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Application of Zhuangzi's View on Death to the Philosophical Counselling - Choi, Cheng In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

The Association Between Interpersonal Relationships and Mental Health in College Students in Macao - Guo, Peiling (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Challenges of Nursery Teachers in the Early Childhood Inclusion Classes: A Qualitative Study of Macao Nursery Teachers - Wu, Ma Lei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Effect of Organizational Justice on Work Engagement Between Foreigner and Local Workers in Macau: The Moderating Effect of Organizational Commitment - Wong, Wai Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Effects of an Aikido Based Psychological Intervention Program in Workplace Stress - Tam, Heng Kun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effects of Family Support, Friends Support, Supervisor Support, Co-worker Support, and Organizational Support to Resilience and its Effects to Work Engagement - Wong, Sio Peng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Financial Valuation of Walmart Inc - Lestro, Gonçalo Nuno das Neves Arrojado (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Financial Valuation of Waste Management, Inc: Daniela Wai Ka, Leong - Leong, Wai Ka (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Future of Cosmetics Marketing Strategy: An Exploratory Study into How Neuromarketing Can Deepen its Understanding - Neto, Andreia Da Conceição (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Idea of the Exemplary Salesian in the Twelve Recorded Dreams of St. John Bosco: A Spiritual and Psychological Consideration - Ho, Ka Fai (University of Saint Joseph, 2022)
This dissertation is an attempt to analyze the twelve selected dreams written or reviewed by St. John Bosco in order to present the notion of an exemplary Salesian. These dreams inspired Don Bosco’s vocation, charism, and dealing with his life’s contingencies and correlate with his pastoral ministry for youth under the social-ecclesiastical context of the nineteenth century. The methodology for this research consists of two approaches: an investigation of their spiritual theology, and Morton T. Kelsey’s approach. In the first part, five dimensions of spiritual theology are explored: (1) the conformity to the truth, (2) the humility and the docility to the Divine will, (3) the discretion and the gravity of seeking the glory of God, (4) the liberty of Spirit with joy, and (5) the guidance of the Spirit. In the latter part, three issues inspired by Kelsey are explored: (1) the personal issue, including the exploration of thought and feeling; (2) the correlation between the dream content and the reality, including images and archetypal symbols associated with experience and memory; (3) the spiritual issue, including one’s openness to God and relation with Him. Through this present research, a model of an exemplary Salesian has been conceptualized, which considers three virtues: health, wisdom, and sanctity. This present study is expected to be beneficial to enhance the faithful’s spirituality. Moreover it is hoped it will provide a healthy stimulus for Salesians to seek to live an excellent Salesian religious life, and to the faithful be devoted Christians in this world as well for the sake of glorifying the Divine mercy
Keywords: Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

The Impact and Attitude of Urban Renewal on Citizen Residents in Macau - Si Cheng Iok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

The Impact of Father-Adolescent Relationship on Child Development in Macao - Lao, Pak Lun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Impact of Macau Teaching Professionalism to Kindergarten teachers' Occupational Identity and Competency: A Study on In-service Teachers' Perception = 澳門教師專業化對幼兒教師職業身份認同和勝任感的影響：來自在職教師的看法 - 張翟 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Indirect Effect of Job Insecurity and COVID-19 Induced Stress on Mental Health through the Mediating Effect of Burnouts and the Moderating Effect of Perceived Social Support among Macau Gaming Employees - Hoi, Lok (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Influence of Official Digital Infographics in Macao during the COVID-19 Pandemic - Ho, Weng In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The Influence of Online Payment Methods on Consumers’ Online Purchase Behavior: The Case of Young People in Macau - Martins, Maria Cordes Aniceto (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Influence of Strengths-Based Intervention to Students’ Engagement and Self-Efficacy in Macau - Jr. Tabilas, Faustino T. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

The Moderating Effect of Job Alternatives Perceptions in the Relationship Between Burnout and Turnover: A Study During the COVID-19 Pandemic in Macao - Fong, Sut Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

The Perception of Skirt Wearing and Masculinity in Contemporary Society: A Case Study in São Paulo, Brazil and Shanghai, China - Chan, Jose Manuel Enesoe (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

The relationship between social support and death anxiety among elderly living alone in Macao - Lo, Pou Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Relationship Between Stress and Emotion Regulation with Students’ Academic Achievement - Cheong, Sin Teng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Relationship Between Work-Life-Balance and Burnout: Effect of Gender and Sector of Activity - Vai, Han Kuoc (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Organisational Psychology (MOP); University of Saint Joseph

Till Death Do (Not) Us Part: Elderlies’ Preparation on Wealth Transmission and the Effectiveness of Testaments in Macao - Chan, Hong Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Community Development (MCD); University of Saint Joseph

To Identify Buyer Behavior Towards Online Shopping Due to Covid-19 Pandemic in Hong Kong - Lio, Cheng Tong (University of Saint Joseph, 2022)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Unity of Knowing and Acting from Christian and Confucian Ethical Practices: An Exegesis of Mark 4:1-20 - Chiang, Sau Kuan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Use and Perception of Visual Communication on Instagram by Macau Residents - Ku, Kit Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Using Online Learning to Enhance Motivation in an English as a Second Language Classroom: An Action Research Study - Kuok, Weng Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Virtual Meetings: How to Increase Communication Effectiveness - Lei, Chio Lan (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Communication and Media (MCM); University of Saint Joseph

Work-Life Balance and Life Satisfaction in Macao: The Mediating Effect of Work Satisfaction - Chan, Lok Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Counselling and Psychotherapy (MCP); University of Saint Joseph

初中教師面對融合學生校園欺凌經驗及應對策略之研究 =: Research on the Experience and Coping Stratrgies of Junior High School Teachers in the Face of Integrated Students' Bullying in Schools - Cheok, Pou Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

初探澳門更生人士在專業工作過程的成功因素=: Explore Successful Factors in Recognition of Professional Work Process for Ex-Offenders - Ip, Ka I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

合作學習法在小學中文科教學中的實施: 以澳門某小學為例 = The Implementation of Cooperative Learning in Primary School Chinese Teaching: A Case Study of a Primary School in Macao - Fong, Hio Man (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

土生葡人和亞洲葡裔在三藩市灣區 =: MACANESE AND LUSO-ASIANS IN THE SAN FRANCISCO BAY AREA - Leong Wong, Un Na (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations PhD in History (D-HIS); University of Saint Joseph; 三藩市; 亞洲葡裔; 土生葡人; 灣區; 身份認同

從混合性研究中探討澳門長者對睡眠健康認知及其相關之因素 =: Exploring Perception on Sleep Health and its Related Factors among Older People in Macau - A Mixed Methods Study - Cheang, Ka Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

探討第29/2020號行政法規對特殊教育教師為特殊需求學生評估的影響 =: Exploring the impact of Administrative Regulation No. 29/2020 on the evalution of the special education teachers for students with special needs - Lo, Chon In (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討透過「五感教學」進行幼兒社交情緒教育之行動研究 =: Action Research on Teaching the Social Emotion in Children by Using on Five-Senses Teaching Approach - Lei Weng I (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門中年男士焦慮狀況、求助態度與自殺意念之相關研究 =: A Correlational Study Between Anxiety and Help-Seeking Attitudes on Suicidal Ideation of Middle-Aged Men in Macau - Lo, Kuan U. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門唐餅文化研究 = A Study of the Culture of Traditional Chinese Pastry in Macau - Pong, Chio Fai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

澳門大學生在內地的就業意向及其影響因素調查=: A Study on Macau Undergraduate Students’ Working Intention in Mainland China - Wu, Zhi Ying (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學教師經營融合班級的困擾與特教專業知能之關係研究 =: The Relationship Between Teachers' Difficulties in Operating Inclusive Classes and the Professional Competence of Special Education in Macao Primary Schools - Lo Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門已婚人士的婚姻質量與社交媒體參與之研究 =: The Study of Marital Quality and Social Media Engagment Among Married People in Macau - Ho, I. Mei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門年輕群體對性別多元態度與態度構成因素之研究 =: The Attitude of the Relative Influential Factors and Gender Diversity on Youth in Macau - Fion, Si Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門幼稚園融合教育專責團隊合作模式之探究 =: A Study on the Cooperation Model of Kindergarten Inclusive Education Collaborative Team in Macau - Li, Xiao Hua (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門戲劇教育發展的演變及挑戰: 以澳門演藝學院戲劇學校為研究對象 =The Growth and Challenges of Theatre Education in Macau: A Case Study of The School of Theatre at the Macao Conservatory - Chan, Ka I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

澳門新任教師職業適應的研究：: 來自在內地與澳門接受師範培養的幼兒教師反饋= Research on the Career Adaptation of New Teachers in Macao Feedback from Kindergarten Teachers who Received Teacher Education in the Mainland and Macau - Kou Mei Kei (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門新入職教師在融合教育的學校中面對的挑戰 =: New Teachers' Challenges in School Which Provided Inclusive Education in Macao - Che, Ka Ian (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門普校教師對融合生的認知印象及接納態度之研究 =: A Study of Teachers's perceptions of cogitve impressions and aceptance attitudes on inclusive students in Macau - Wong, Tong Cheong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門普通學校教師任教融合生的教學困擾和支援服務需求之研究=: A Study of the Teaching Distress and Needs of Supportive Service of Students with Special Educational Needs Taught by General School Teachers in Macau - Kong, Chi Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門融合教師職業壓力來源研究: 以澳門某私立小學教師為例 = Occupation al Stress sources of inclusive education teachers in Macau - A study on primary shcool teachers in a private school - U, Ka Chon (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門長者對樂齡科技的感知及應用動機研究 =: Elderly's Perception and Motivation for the Application of Gerontechnology in Macau - Lee, Hou Sun (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

澳門露宿者服務社工在新冠疫情情間的工作與挑戰 = The Opportunities and Challenges Facing Macau Social Workers Who Work with Homeless People During the Pandemic of 2020 : A Case Study - Wong, Choi Leng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Social Work (MSW); University of Saint Joseph

街舞在澳門的在地化的研究1980-2020=: Localization of Street Dance in Macau 1980-2020 - Tai, Chou Wai (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of History & Heritage Studies (MHHS); University of Saint Joseph

運用正念呼吸練習支援兒童專注力發展之行動研究 =: An Action Research on using mindfulness breathing exercise to support the development of children's concentration - 王嘉蘭 (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph